Leprosy and migration: spatial correlation in a hyperendemic State in the brazilian Amazon (Research, Society and Development, 2021)
This study aimed to identify the spatial dependence on leprosy detection rates in the general population and in children under 15 years of age with the migration proportion, in Pará state. The research was carried out with an ecological study design in a historical series of leprosy new cases, between 2006 and 2015, from the Ministry of Health's Notifiable Diseases Information System database, referring to the State. The temporal evolution of the general detection rate, standardized by age, presented geographically, identified a corridor of great hyperendemicity of the disease, in the Southwest-Southeast of the State and two municipalities clusters, also of very hyperendemicity, on the border with Tocantins and Maranhão States. The spatial analysis showed that the average rates in the general population and under 15 years of age and the proportion of migration showed positive spatial autocorrelation, allowing to identify clusters located in the Southeast, Southwest, North, and Northeast areas of the State. Mineral exploration and agriculture projects are concentrated in these areas, where two Hydroelectric Power Plants were built in the 1960s and 2000s, favored by a consolidated road and rail network that is used for the flow of products and for the intense people migratory flow. This research shows that leprosy has a high magnitude with active transmission characteristics and that 2/3 of the territorial area expresses hyperendemicity, highlighting it as a serious public health problem in Pará state.